MANAGEMENT OF OCCUPATIONAL HEALTH AND SAFETY - Kelloway, E. Kevin; Francis, Lori; Gatien, Bernadette; Belcourt, Monica (Nelson, 2021)
This text is intended to give the HR manager and the HR professional a basic understanding of the elements that combine to create an effective occupational health and safety program. Throughout the text students are provided with current examples, clear definitions of technical terms, and links to the vast amount of information found on the Internet